NLRP3 Inflammasome Upregulates PD-L1 in Ovarian Cancer and Contributes to an Immunosuppressive Microenvironment - Pan W; Jia Z; Du J; Chang K; Liu Y; Liu W; Zhao X; Tan W (ImmunoTargets and Therapy)
Wenjing Pan,1,* Zhaoyang Jia,1,* Jingtong Du,1,* Kexin Chang,2 Yiming Liu,2 Wei Liu,1 Xibo Zhao,3 Wenhua Tan1 1Department of Gynecology, The Second Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, 150081, People’s Republic of China; 2Department of Gynecology Oncology, Harbin Medical University Cancer Hospital, Harbin, Heilongjiang, 150081, People’s Republic of China; 3Department of Gynecological Oncology, Sun Yat-Sen Memorial Hospital of Sun Yat-Sen University, Guangzhou, 510120, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xibo Zhao; Wenhua Tan, Email zhaoxb8@mail.sysu.edu.cn; tanwenhua1962@126.comIntroduction: The NLRP3 inflammasome has been implicated in the initiation of inflammation and tumorigenesis; however, its role in epithelial ovarian cancer (EOC) remains unclear.Methods: This study employed high-throughput sequencing data, ELISA, clone formation assay, Western blot, and flow cytometric analysis to investigate the specific role of the NLRP3 inflammasome in EOC.Results: NLRP3 was highly expressed in human EOC tissues and correlated with an unfavorable prognosis. Activation of the NLRP3 inflammasome by LPS and ATP promoted EOC cell proliferation and increased IL-1 and PD-L1 levels. MCC950, a NLRP3 inflammasome blocker, reduced IL-1 and PD-L1 levels and diminished tumor-immune suppressive cells, such as myeloid-derived suppressor cells (MDSCs), tumor-associated macrophages (TAMs), and PD-1+ CD4+ T cells, in a murine model of ovarian cancer. This intervention also suppressed tumor growth.Conclusion: Our investigation revealed the pro-tumorigenic role of the NLRP3 inflammasome and its regulation of PD-L1 expression in EOC. Blockade of the NLRP3 inflammasome led to reduced PD-L1 expression, fewer immunosuppressive cells, and suppressed tumor growth. These findings suggest that targeting the NLRP3 inflammasome-PD-L1 axis could be a novel treatment approach for ovarian cancer.Keywords: NLRP3 inflammasome, PD-L1, immunosuppressive cells, EOC, inflammation